Rekayasa Ulang Sistem Informasi Beasiswa IKAPCR - Apriantoni Apriantoni; Indah Lestari; Dadang Syarif Sihabudin Sahid (Ikatan Ahli Informatika Indonesia (IAII), 2020)
The Politeknik Caltex Riau’s Alumni Association (IKAPCR) has a scholarship information system that contains a Decision Support System (DSS) and scholarship financial management. The IKAPCR scholarship information system requires a reengineering process of several features to meet the needs of system users at the management level. Evaluation of beta testing on IKAPCR scholarship information system shows that the system runs normally as it should based on user requirements, it is informative and innovative, and able to accelerate the scholarship acceptance selection process. While its weaknesses are the process of data integration with the academic system of Politeknik Caltex Riau (PCR), regular reminder donation services via e-mail and SMS, data management on semester payments for scholarship recipients and additional variations graphic info for the analysis process. Therefore, this system needs a reengineering process to improve efficiency at each mechanism of the process. Testing with WebQual of 117 students and 33 PCR alumni, the accuracy of the student respondents was 79.7% which showed that respondents agreed that the quality of the web was good and 80.2% of the alumni respondents indicated that respondents strongly agreed on good web quality.